2001
DOI: 10.1016/s0009-2509(00)00270-0
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen production by catalytic cracking of methane over nickel gauze under periodic reactor operation

Abstract: The catalytic cracking of methane over nickel gauze is proposed as an attractive alternative for the production of CO-free hydrogen. The catalyst deactivates due to intensive coke deposition. Therefore, the reactor was operated periodically with the reaction followed by the catalyst regeneration by burning of coke in oxidative atmosphere. The optimal reaction performance was found to consist of reaction periods of 4 min followed by 4 min regeneration periods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0
2

Year Published

2003
2003
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(39 citation statements)
references
References 7 publications
0
37
0
2
Order By: Relevance
“…First, carbon can form as a result of reactions over a catalyst. This process has been very well studied over Ni, Fe, and Co, both for catalytic applications [9][10][11][12][13][14][15][16] and for "dusting", also known as "dry corrosion", the problem of pitting when steels are exposed to hydrocarbons at high temperatures [17,18]. The mechanism on each of these metals involves deposition of a carbon source onto the metal surface, dissolution of the carbon into the bulk of the metal, and finally precipitation of carbon as a graphite fiber at some surface of the metal particle.…”
Section: Introductionmentioning
confidence: 99%
“…First, carbon can form as a result of reactions over a catalyst. This process has been very well studied over Ni, Fe, and Co, both for catalytic applications [9][10][11][12][13][14][15][16] and for "dusting", also known as "dry corrosion", the problem of pitting when steels are exposed to hydrocarbons at high temperatures [17,18]. The mechanism on each of these metals involves deposition of a carbon source onto the metal surface, dissolution of the carbon into the bulk of the metal, and finally precipitation of carbon as a graphite fiber at some surface of the metal particle.…”
Section: Introductionmentioning
confidence: 99%
“…In this case, the methane decomposition step was performed for 1 h following which the catalyst was regenerated using an oxidation-reduction cycle. There was no apparent decrease in catalytic activity throughout the 12 cycles studied at 723 K. Similarly, Monnerat et al [51] have investigated the cyclic process (methane decomposition and air regeneration) over a Ni gauze catalyst (Ni-grid with Raney type outer layer). Their studies revealed an optimal reaction performance when the cycle consisted of 4 min of reaction period followed by 4 min of regeneration period.…”
Section: Step-wise Reforming Of Hydrocarbonsmentioning
confidence: 94%
“…The main advantages of this kind of catalyst are the regular open structure and the exibility that enables to use them in structured catalytic beds . In order to increase the speciÿc surface area of bulk nickel, a Raney-type outer layer was formed on the metal surface (Wainwright, 1997;Monnerat et al, 2001;Kiwi-Minsker, 2002). Experiments were performed with the modiÿed nickel gauze (∼ 210 mg), placed in the middle part of the reactor in a rolled form (length 20 -30 mm) between two inert packings of quartz beads.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, we reported an attractive method to produce carbon oxide-free hydrogen by catalytic cracking of methane over nickel gauze (Monnerat, Kiwi-Minsker, & Renken, 2001). The catalyst deactivates due to intensive coke deposition.…”
Section: Introductionmentioning
confidence: 99%